The Contribution of Environmental Vocabulary and Reading Interest in EFL Students’ Writing Skills of Exposition Texts - Ali, Ririn Fujiarti; Thahar, Harris Effendi (Universitas Pendidikan Mandalika, 2024)
This research is motivated by the low interest in reading that students have. The low interest in reading makes the lack of vocabulary mastery. The purpose of this study is to explain the contribution of environmental vocabulary mastery and reading interest to students' expository text writing skills. This type of research is quantitative research. The method used in this research is descriptive method. The research data were obtained from the final test results of exposition text writing skills of class X students of SMK Negeri 1 Bandar Sungai Kijang, Pelalawan Regency, Riau. Instruments to collect vocabulary mastery data using objective tests, reading interest using questionnaire techniques / research instruments, while to collect data on exposition text writing skills using written tests. The technique of analyzing data used in this research is descriptive and inferential statistics. The results showed that there was a significant contribution between the mastery of vocabulary in the environmental field to the skill of writing exposition texts of Class XI students of SMK Negeri 1 Bandar Sungai Kijang Regency Pelalawan Riau. This means that the better the mastery of vocabulary in the environmental field of students, the better the degree of writing skills of the student's exposition text. Then there is a significant contribution between reading interest and exposition text writing skills of Class XI students of SMK Negeri 1 Bandar Sungai Kijang Regency Pelalawan Riau. This means that the better the student's interest in reading, the higher the degree of skill in writing the student's expository text. Finally, there is a simultaneous contribution between the mastery of vocabulary in the environmental field and reading interest to the exposition text writing skills of Grade XI students of SMK Negeri 1 Bandar Sungai Kijang Regency Pelalawan Riau.